Modification of surface hydrophilicity of dental materials by ozone - Artilia, Ira (Padjadjaran Journal of Dentistry, 2019)
Introduction: Gypsum, Portland, and apatite cement, and gypsum have been developed as dental materials for a long time. Similarity of the three materials leads to some relevant approaches to improve the characteristic of dental materials. Water reducing agent is commonly used in detergent or soap and also used as a conventional method in the cement industry to increase the handling and mechanical property. Cement paste mixed with water reducing agent is more flowable (ease handling), and the set mass is harder (mechanical property increased). However, it has a problem with biomaterial cement due to the biocompatibility. This water reducing agent is harmful to living tissue. Therefore, a new approach will be demonstrated in this research. Methods: In this study, the hydrophilicity of cement powder was modified by ozone gas treatment. Ozone gas treatment will be applied to modify the hydrophilicity of cement particles; therefore, it can act similar to the water reducing agent. Results: The hydrophilicity of gypsum, Portland, and apatite cement powder was significantly increased after ozone gas treatment. The hydrophilicity improvement of cement powder increased the ability of water to interact with the cement powder. The benefit is the flowability improvement of cement paste. Therefore, the manipulation index would also be increased. The mechanical property would be increased because the water added for manipulation was decreasing. Conclusion: Ozone gas treatment could improve the hydrophilicity of gypsum, Portland, and apatite cement powder.Keywords: Gypsum, Portland, apatite cement, hydrophilic, ozone